2018
DOI: 10.21494/iste.op.2018.0221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-idealities on the Performance of InAs/(In)GaAsSb/GaSb Tunnel FETs

Abstract: Measured InGaAsSb/InAs nanowire TFETs showing both, sub-60mV/dec slope and high ON-current, are simulated using calibrated TCAD. The focus is laid on the impact of non-idealities, such as hetero-interface traps, oxideinterface traps, and bulk traps on device characteristics. Simulated temperature-dependent transfer curves are in good agreement with the measured data which validates the simulation setup. It is found that trap-assisted tunneling involving bulk traps adjacent to the hetero-junction is primarily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It is worth mentioning that our results, in this case study, are in agreement with the results of [23] and [35] which reported that the impact of bulk traps on the performance of hetero-junction TFETs is minor while the impact of heterointerface traps and oxide-interface traps are dominant. So, it is important to investigate the impact of oxide-interface traps on the transfer characteristics of the proposed SS-TFET design.…”
Section: Impact Of Non-idealitiessupporting
confidence: 92%
See 1 more Smart Citation
“…It is worth mentioning that our results, in this case study, are in agreement with the results of [23] and [35] which reported that the impact of bulk traps on the performance of hetero-junction TFETs is minor while the impact of heterointerface traps and oxide-interface traps are dominant. So, it is important to investigate the impact of oxide-interface traps on the transfer characteristics of the proposed SS-TFET design.…”
Section: Impact Of Non-idealitiessupporting
confidence: 92%
“…Additionally, the impact of variation of the effective oxide thickness (EOT) is presented. Moreover, the influence of different types of non-idealities like hetero-interface traps, oxide interface traps and bulk traps, which may arise from fabrication processes [22,23], on the device performance is studied. Finally, the conclusions are drawn in the last section.…”
Section: Introductionmentioning
confidence: 99%
“…As the gate underlap distance from source end increases, the influence of electrostatic gate control over the active region of the device decreases. 21 Hence, the magnitude of band lowering at the hetero interface decreases despite the shell radius as depicted in Fig. 4(ii).…”
Section: Resultsmentioning
confidence: 88%
“…Based on recent TCAD modeling works of trap-related effects in a start-of-the-art experimental III-V TFET [7,8], we here propose to extend an existing Verilog-A compact model for an ideal TFET [9,10] to the respective parasitic effects of junction bulk traps and oxide interface traps. Therefore, for the first time, we manage to elucidate the impact of traps in a realistic TFET on its circuit-level power-performance (PP) metrics through SPICE simulations on a ring oscillator (RO) circuit test bench.…”
Section: Introductionmentioning
confidence: 99%